Bifunctional 3D-MOF-based nanoprobes for electrochemical sensing and nanozyme enhanced with peroxidase mimicking for colorimetric detection of acetaminophen. (March 2022) - Nataraj, N.; Chen, T.-W.; Gan, Z.-W.; Chen, S.M.; Hatshan, M.R.; Ali, M.A.
Abstract: The outgrowth of the zeolitic imidazole framework (ZIF-67) with substantial benefits was significantly used in the present study. The attractive properties of ZIF-67 are envisioned to develop a dual-functional sensing platform as electrochemical and colorimetric for acetaminophen detection. Co-ZIF-67 was developed as a synthesis-controlled material via three different preparation techniques as ZIF-67-C, ZIF-67-A, and ZIF-67-H. ZIF-67-C prepared via simple co-precipitation strategy in room temperature acquired rhombic dodecahedral structure with increased electrocatalytic activity. ZIF-67-C nanozyme exhibits enzymatic activity with intrinsic peroxidase mimicking and higher electron affinity than ZIF-67-A and ZIF-67-H. The well-developed ZIF-67-C without further aggregation and a steadily build structure resulted in an enhanced response. While the higher chance of aggregation and irregular arrangements of ZIF-67-A and ZIF-67-H resulted in lower performance toward acetaminophen detection. Moreover, the absorption of 3, 3 ', 5, 5' – tetramethylbenzidine (TMB) molecules could lower the diffusion distance leading to improved peroxidase mimicking activity. Nanozyme ZIF-67-C effectively oxidizes TMB to TMBox product and with hydroxyl radicals ( OH) generation from H2 O2 decomposition. Michaelis-Menten and Lineweaver Burk's model was estimated. The LOD was 0.014 μM (electrochemical) and 0.034 μM (calorimetric). The real samples as river water and lake water show good recovery in both sensing modes. The high surface area, improved electrical conductivity, high porosity of the prepared ZIF-67-C sample is beneficial for dual sensing applications and determined to be used in several applications. Highlights: Different synthesis routes-based comparison study on Co- zeolitic imidazole framework (ZIF)-67 is reported. The nanocatalyst-ZIF-67 was used in dual sensing of acetaminophen. ZIF-67 was used as an excellent electrocatalyst in electrochemical detection and an artificial enzyme in colorimetry detection. ZIF-67 oxidized tetramethylbenzidine molecules to ox-tetramethylbenzidine with the presence of acetaminophen and H2 O2 . Lower detection limit about 0.014 μM and 0.034 μM was obtained in both the sensing applications.